Educar para la democracia (Ensayos) - Ayala Mora, Manuel Enrique (2022)
This essay discusses the nature of Education for Democracy, the antecedents of the teaching of Civics, its pedagogical foundations, and didactic criteria. It starts from a discussion of the educational reforms carried out in Ecuador since the end of the 20th century and the contribution of the proposal of the Baccalaureate Curricular Reform Program executed by the Universidad Andina Simón Bolívar Sede Ecuador with a pilot and experimental character at the national level, until 2002. From this point, some general lines are established for a Civics program that can fill the void left by the Education for Citizenship subject, in charge of covering the contents of Education for Democracy as of the 2010 reform. This program aims to train young people to recognize responsibility and social solidarity, exercise their rights, fulfill their obligations, and define mechanisms that ensure their participation in the institutions of the political system. The program is conceived as a constant throughout the educational system, highlighting Ecuador’s reality as a unit of diversity. The proposal is not based on abstract statements but concrete reality, encouraging students to understand their homeland.